PROFITABILITY DASH BOARD DESIGN TO PROVIDE FINANCIAL PERFORMANCE ANALYSIS WITH USER CENTERED DESIGN METHOD - yosvi Andri; ahmad Nurul Fajar (SEAN Institute, 2022)
The financial performance report is a very important thing for the company. For this reason, the company must be able to measure and evaluate the financial performance in order to achieve the results that have been set. One of the financial performance reports that must always be informed is the company's profit and loss report. The report contains all information regarding the income and expenses. The importance of this information must be communicated to stakeholders, so that it can assist in making strategies and making decisions for better results. Based on interviews conducted with several branch heads at the company, they wanted a more simple and informative report, such as a dashboard display. This dashboard is expected to help them in getting information and analysis that is easy to understand. To accommodate these needs, research was conducted on the design of the profitability dashboard to improve company performance. In this study, we develop a dashboard related to all information about profit and loss for each branch at company. The information provided in a dashboard designed such as data on Net Interest Income, Non Interest Income, Loan Recovery Income, OPEX, Shadow Income, Provision Expenses and other information that will be packaged in an interactive dashboard with user centered design method using the Microsoft Power BI application.